The Relevance of Al-Shaibani's Thought in the Modern Era - Akbar, Akbar Muhamad Ashoni; Muhidin, Muhidin (Prodi Hukum Ekonomi Syariah STAIN Teungku Dirundeng Meulaboh, 2025)
This paper explores the economic thought and legal framework of Islamic economics during the era of Al-Syaibani, a significant figure in the history of Islamic economic thought known for his contributions to understanding the concepts of work and production within an Islamic context. Al-Syaibani emphasizes the role of humans as stewards (khalifah) on earth, responsible for utilizing resources in a manner that promotes the welfare of all beings. In his view, production activities are not merely about seeking profit but are also part of the obligation to create sustainable prosperity for humanity. His renowned work,